Anti-inflammatory Activity of Temulawak Nanocurcuminoid Coated with Palmitic Acid in The Sprague Dawley Rat - Rini Novita; Laksmi Ambarsari; Syamsul Falah; Popi Asri Kurniatin; Waras Nurcholis; Latifah K Darusman (Current Biochemistry, 2015)
Temulawak or Curcuma xanthorrhiza Roxb, is usually used as traditional medicine (herbal medicine) that has antioxidant, anticancer, antihyperglycemic, anti-inflammatory, hepatoprotective and gastroprotective properties. The main components contained in temulawak responsible for its efficacy as a medicine are xantorhizol and curcuminoid. Curcuminoid has drawbacks, which are difficult to absorb and very quickly metabolized by the body, so that limit its bioavailability. The use of solid lipid nanoparticle carrier system (SLN) in form of palmitic acid, is known to improve the bioavailability of curcuminoid. This study aims to find the effective dose of nanocurcuminoid coated with palmitic acid that can be used as an anti-inflammatory agent. The methods used in this study, include the production of nanocurcuminoid with homogenization and ultrasonication methods, determination of particle size, polydispersity index, entrapment efficiency and anti-inflammatory activity test through rat feet edema. Nanocurcuminoid obtained in this study was 561.53 nm in size, with polydispersity index 0.309 and concentrations of curcuminoid absorbed and entrapment efficiency were 0.61±0.031 mg/mL, 58.93±3.021%, respectively. Anti-inflammatory activity of nanocurcuminoid through treated Sprague Dawley rats, showed that there were no significant difference compared with the positive control, curcuminoid extracts and empty nanoparticle. These results indicate that nanocurcuminoid with 175, 200 and 250 mg/kg.bw in doses, has greater anti-inflammatory activity (31.70%) compared to the other treatments.